Using Nucs in Beekeeping Operations - J. D. Ellis (EDIS)
This revised 9-page illustrated fact sheet by James D. Ellis discusses the merits of using nucleus colonies, or nucs, which are smaller versions of full-sized Langstroth hives. The publication explains how to create and manage nucs and how to use them to control swarming, strengthen production colonies, re-queen hives, hive swarms, produce queens to sell to other beekeepers, and in general strengthen and expand a beekeeping operation. Published by the UF Department of Entomology and Nematology. http://edis.ifas.ufl.edu/in869